Educational training and technical instructions for government equipment in Sidenreng Rappang City - Andi Uceng; Sam Hermansyah; Irwan (IHSA Institute, 2023)
This study describes a training needs analysis for training and technical advice in the City of Sidenreng Rappang. This research reveals that there are 12 priority programs that the Sidenreng Rappang government must immediately implement for its government apparatus. Some of them train how to prepare proper financial reports and train how to use social media for government agencies. This only aims to improve the quality of the state apparatus which ultimately leads to satisfactory public services. This study uses the concept of human resource management and training of government officials. The method used in this research is a qualitative research method. The purpose of this training is for Sidenreng Rappang city officials to be able to prepare official letters in accordance with statutory regulations. This is Government Decree No. 80, issued in 2012 by the Minister for Strengthening the State Apparatus and Forms of Bureaucracy. Specific topics and speakers according to their performance